2013
DOI: 10.1007/s11764-013-0284-8
|View full text |Cite
|
Sign up to set email alerts
|

Is it safe and efficacious for women with lymphedema secondary to breast cancer to lift heavy weights during exercise: a randomised controlled trial

Abstract: Purpose: Resistance exercise has great potential to aid in the management of breast cancer-related lymphedema (BCRL); however, little is known regarding optimal exercise prescription. The pervasive view is that resistance exercise with heavy loads may be contraindicated, disregarding the dose-response relationship that exists between the load utilised in resistance exercise and the magnitude of structural and functional improvements. No previous research has examined various resistance exercise prescriptions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
167
0
22

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(201 citation statements)
references
References 45 publications
12
167
0
22
Order By: Relevance
“…It is estimated that around 60 % of patients present one upper-body symptom, which affects breast cancer patients' daily activities and reduces significantly their quality of life [31]. Others have previously shown similar results to ours [34][35][36][37][38][39][40], despite the fact that most of these studies involved longer interventions. We are encouraged that shorter interventions of even 12 weeks appear effective to reduce such treatment side effects achieving similar improvements.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It is estimated that around 60 % of patients present one upper-body symptom, which affects breast cancer patients' daily activities and reduces significantly their quality of life [31]. Others have previously shown similar results to ours [34][35][36][37][38][39][40], despite the fact that most of these studies involved longer interventions. We are encouraged that shorter interventions of even 12 weeks appear effective to reduce such treatment side effects achieving similar improvements.…”
Section: Discussionsupporting
confidence: 78%
“…As has been reported in several previous studies [34,47,48], women in the exercise group did not present significant swelling in the affected arm, further demonstrating that combined exercise interventions do not increase the risk of developing or exacerbating lymphedema [49,50]. It is hoped that this growing research evidence finally dismisses reticence to prescribe resistance training for patients with lymphoedema.…”
Section: Discussionsupporting
confidence: 69%
“…Of the sixteen studies involving patients in active treatment [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] , six demonstrated that, compared with the control group, the intervention group experienced significant improvements in qol 30,31,33,[38][39][40]43 . In the thirteen post-treatment intervention studies 10,12,14,[45][46][47][48][49][50][51][52][53][54] , two reported similar significant differences between groups 46,49 .…”
Section: Quality Of Lifementioning
confidence: 99%
“…Few adverse events resulting from exercise were reported in the systematic reviews and rcts. Participants with lymphedema also received qol benefits, and aerobic and resistance exercises were both considered safe for women who had undergone breast and axillary surgery [10][11][12][13][14] .…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation